Perceived Value of Information Attributes: Accounting for Consumer Heterogeneous Preference and Valuation for Traceable Agri-Food - Ruifeng Liu; Jian Wang; Jiahao Liang; Hengyun Ma; Fei Liang (Foods, 2023)
Information attributes characterize traceable agri-food. The perceived value of information attributes influences consumers’ preferences for traceable agri-food, consisting of two dimensions, predictive value and confidence value. We examine heterogeneous preferences and willingness to pay (WTP) in China’s traceable agri-food market. Using the choice experiments, we explore how the traceability information, certification type, region of origin, and price influence Chinese consumers’ Fuji apple choices. We identify three consumer classes by a latent class model: certification-oriented class (65.8%), price-sensitive and origin-oriented class (15.0%), and no-buy class (19.2%). The results show that consumer sociodemographic characteristics, predictive value, and confidence value are the heterogeneous sources that determine their preferences for Fuji apple information attributes. Specifically, consumers’ age, family income per month, and whether the family has children under 18 significantly impact the membership probability of consumers in both certification-oriented and price-sensitive and origin-oriented classes. Consumers’ predicted value and confidence value significantly impact the membership probability of consumers in the certification-oriented class. In contrast, consumers’ predicted value and confidence value have no significant impact on the membership probability of consumers in price-sensitive and origin-oriented class.